Effect of Concomitant Birth Defects and Genetic Anomalies on Infant Mortality in Tetralogy of Fallot. Issue 14 (19th June 2017) - Jernigan, Eric G.; Strassle, Paula D.; Stebbins, Rebecca C.; Meyer, Robert E.; Nelson, Jennifer S.
Abstract : Background: A substantial proportion of infants born with tetralogy of Fallot (TOF) die in infancy. A better understanding of the heterogeneity associated with TOF, including extracardiac malformations and chromosomal anomalies is vital to stratifying risk and optimizing outcomes during infancy. Methods: Using the North Carolina Birth Defects Monitoring Program, infants diagnosed with TOF and born between 2003 and 2012 were included. Kaplan‐Meier survival curves were used to estimate cumulative 1‐year mortality, stratified by the presence of concomitant birth defects (BDs) and chromosomal anomalies. Multivariable logistic regression was used to estimate the direct effect of each concomitant BD, after adjusting for all others. Results: A total of 496 infants with TOF were included, and 15% ( n  = 76) died. The number of concomitant BD systems was significantly associated with the risk of death at 1‐year, p  < 0.0001. Specifically, the risk of mortality was 8% among infants with TOF with or without additional cardiac defects, 16% among infants with TOF and 1 extracardiac BD system, 19% among infants with 2 extracardiac BD systems, and 39% among infants with ≥ 3 extracardiac BD systems. After adjustment, concomitant eye and gastrointestinal defects were significantly associated increased with 1‐year mortality, odds ratio 2.83 (95% confidence interval, 1.08–7.32) and odds ratio 4.43 (95% confidence interval, 1.57, 12.45), respectively. Infants with trisomy 13 or trisomy 18 were also significantly more likely to die, p  < 0.0001. Conclusion: Both concomitant BDs and genetic anomalies increase the risk of mortality among infants with TOF. Future studies are needed to identify the underlying genetic and socioeconomic risk factors for high‐risk TOF infants. Birth Defects Research 109:1154–1165, 2017. © 2017 Wiley Periodicals, Inc.